The Doubles in Julien Gracq's Au Château d'Argol - Andrée Douchin-Shahin (Studies in 20th & 21st Century Literature, 1984)
In Julien Gracq's Au Château d'Argol, the resolution of a psychological double (as in the Doppelgänger novels) opens onto a metaphysical quest. In the process, doubling becomes so compounded that the narrative resembles a kaleidoscopic pattern of multiple reflections. Gracq's personal search into the nature of man is set against other hypotheses and formulations such as philosophical systems, religion, psychoanalysis, literature, music, etc. In the novel, man's dualism is viewed as an inescapable fact. However, even though the dogma of the Redemption is rejected, man, in spite of his "flaw," is held responsible for the acts he wills.
Keywords: Julien Gracq; Au Château d' Argol; psychological double; Doppelgänger; metaphysical; self; nature of man; philosophy; religion; psychoanalysis; literuate; man' s dualism; dualism